Hepatoprotective effects of Orthosiphon stamineus extract on thioacetamide-induced liver cirrhosis in rats - Alshawsh, Mohammed A.; Abdulla, Mahmood Ameen; Ismail, Salmah; Amin, Zahra A. (Hindawi, 2011)
Orthosiphon stamineus as medicinal plant is commonly used in Malaysia for treatment of hepatitis and jaundice; in this study, the ethanol extracts were applied to evaluate the hepatoprotective effects in a thioacetamide-induced hepatotoxic model in Sprague Dawley rats. Five groups of adult rats were arranged as follows:Group 1 (normal control group), Group 2 Thioacetamide (TAA) as positive control (hepatotoxic group), Group 3 Silymarin as a well-known standard drug (hepatoprotective group), and Groups 4 and 5 as high and low dose (treatment groups). After 60-day treatment, all rats were sacrificed. The hepatotoxic group showed a coarse granulation on the liver surface when compared to the smooth aspect observed on the liver surface of the other groups. Histopathological study confirmed the result; moreover, there was a significant increase in serum liver biochemical parameters (ALT, AST, ALP, and Bilirubin) and the level of liver Malondialdehyde (MDA), accompanied by a significant decrease in the level of total protein and Albumin in the TAA control group when compared with that of the normal group. The high-dose treatment group (200mg/kg) significantly restored the elevated liver function enzymes near to normal. This study revealed that 200 mg/kg extracts of O. stamineus exerted a hepatoprotective effect.